ANALISIS SEKTOR PERTANIAN, KEHUTANAN, PERIKANAN TERHADAP PDRB DI KABUPATEN LAMONGAN - Ahmad Rosyid Ridlo; Dwi Susilowati (Program Studi Ekonomi Pembangunan, 2018)
This research aims to analyze the role of the agricultural sector to Gross Regional Domestic Product of Lamongan year 2011-2015. This study uses secondary data in the form of time series data from 2011-2015. The analysis used are Location Quotient (LQ) and the Shift Share. Based on the results of the analysis of the merger value Statistics Location Quotient (SLQ) and Dynamic Location Quotient (DLQ) the subsector of forestry and agriculture include the has excellent sector. The results of the analysis of Shift Share indicate that the growth of the agricultural sector in East Java Province a positive effect on the growth of the agricultural sector, foresty sector, fishery sector in Lamongan. Keywords: Location Quotient (LQ), Shift Share, GDP, Agricultural Sector, Foresty Sector, Fishery Sector.